(untitled) (Revista Brasileira Multidisciplinar, 2013)
This paper aims at contributing to biological and ecological knowledge about Hoplosternum littorale by studying its diet in the Vacacaí River, RS. With this aim, samples were taken in all seasons in four points selected along the Vacacaí River, using gill nets with meshes 1.5, 2.0, 2.5, 3.0, 4.0; 5.0, 6.0 and 8.0 cm between adjacent knots. The nets remained in the water for 24 hours, being revised every six hours. The fish which was caught was fixed in 10% formalin and later preserved in 70% alcohol. The specimens were weighed, measured and had the digestive tract removed for diet analysis. The items found in stomach contents were separated into six categories: Insects, Mollusks, Detritus/Silt, Vegetables, Scales and Nematodes, each category being analyzed by frequency of occurrence and volumetric method, being combined to obtain the Feeding Index" (IAi). The stomach repletion index (SRI) and Repletion Index (RI) were also estimated to assess the feeding activity according to the circadian rhythm. The most important items in the diet of this species according to IAi were insects, sediment and plant. H. littorale showed greater feeding activity in early morning, coinciding with greater capture also in reviewing this time, suggesting a nocturnal activity.